2008
DOI: 10.1111/j.1423-0410.2008.01045.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of tranexamic acid administration during total knee arthroplasty

Abstract: Routine administration of TA during total knee arthroplasty to patients without history of thromboembolic disease is associated with a 67% reduction in RBC transfusions and, in those transfused, with a reduction in the number of units administered. TA treatment was not associated with an increase in thromboembolic complications. Transfusion costs are significantly reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
65
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 33 publications
9
65
1
1
Order By: Relevance
“…But like most other studies, [3], [9], [14] our study also confirmed that the TXA, even topically has no risks. Although our study showed similar results for both groups it is seems but if any increased risks of thromboembolism did exist with this drug it would be lesser with intraarticular administration than IV administration.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…But like most other studies, [3], [9], [14] our study also confirmed that the TXA, even topically has no risks. Although our study showed similar results for both groups it is seems but if any increased risks of thromboembolism did exist with this drug it would be lesser with intraarticular administration than IV administration.…”
Section: Discussionsupporting
confidence: 77%
“…The 1 hour after release of tourniquet is the crucial time when this drug reaches its maximal hemostasis . [9], [14] In our study we open the suction drain tube after an hour of application and still have managed excellent results, still proving that this 1 hour is the most important time for action of this drug"(TXA).The maximum plasma concentration is achieved in 30 min after intramuscular administration. [24], [25] Also the half-life of the drug is less than 3 hour, [2], [3], [10] and therefore there is a accelerateddecrease in plasma levels of this drug.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Tranexamic acid is 10 times stronger in vitro than EACA. In total knee arthroplasty, prophylactic administration significantly reduces blood loss up to 50% and decreases transfusion requirements without increasing the risk of thromboembolic signs (Alvarez et al, 2008;Cid & Lozano, 2005;Lozano et al, 2008). Optimal technique would be with two tranexamic acid bolus (each of them 10-15 mg/Kg), one before surgery and another when letting the air out of the tourniquet.…”
Section: Synthetic Antifibrinolyticsmentioning
confidence: 99%